Tingkat Tutur Bahasa Jawa Masyarakat Samin Desa Klopodhuwur Kabupaten Blora - bekti setio astuti (Jurnal CULTURE (Culture, Language, and Literature Review), 2015)
Samin community communicate by using Ngoko Javanese language because they believe that all people have the same position. But with the growing age, Samin people now know the Javanese speech levels. This is because they have a lot of associations with nonSamin people in buying and selling, community organization and others. Samin community in Klopodhuwur village use Krama Javanese language because of the participants. This does not mean that they do not run the Samin teachings. Samin community in Klopodhuwur village are still running the teachings, because they have the honesty and sincerity as a manifestation of Samin teaching. Keywords: participants, Javenese speech level, Samin community, Samin teaching